Effects of Finapux® in combination with Ralgro® and Synovex® on performance and carcass characteristics of steers and heifers - Kuhl, Gerry L.; Simms, D.; Ritter, R.; Houghton, P.; Hartman, Paul D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five field trials were conducted with 762 steers and heifers to evaluate Finaplix® in combination with Ralgro® or Synovex® for growing and finishing programs. Effects on cattle performance and carcass characteristics were inconsistent across trials. However, in general, implanting cattle with Finaplix and either Ralgro or Synovex tended to result in increased gain, final weight, and carcass weight, with little effect on backfat, loin eye area or kidney, heart, and pelvic fat. Marbling score and the percentage of cattle grading choice tended to be reduced slightly, although this was not usually significant.
Keywords: Beef; Finaplix®; Ralgro®; Synovex®; Performance; Steers; Heifers; Carcass